2014
DOI: 10.1039/c4cc05164e
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in the chemistry of endohedral metallofullerenes

Abstract: Putting metal atoms or metallic clusters into fullerenes has generated a new class of hybrid molecules, defined as endohedral metallofullerenes (EMFs), possessing novel structures and fascinating properties which are different from those of empty fullerenes. In particular, it has been revealed that the chemical properties of the cage carbons of EMFs depend strongly on the nature of the internal metallic species, such as their electronic configuration, location and even motion. Since the first report describing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 81 publications
(140 reference statements)
4
85
1
Order By: Relevance
“…[2] Surprisingly,o nly one benzyl moiety is attached to the cage,i ns harp contrast to the addition of two benzyl radicals to Sc 3 N@I h -C 80 . [2] Surprisingly,o nly one benzyl moiety is attached to the cage,i ns harp contrast to the addition of two benzyl radicals to Sc 3 N@I h -C 80 .…”
Section: Angewandte Chemiesupporting
confidence: 63%
See 1 more Smart Citation
“…[2] Surprisingly,o nly one benzyl moiety is attached to the cage,i ns harp contrast to the addition of two benzyl radicals to Sc 3 N@I h -C 80 . [2] Surprisingly,o nly one benzyl moiety is attached to the cage,i ns harp contrast to the addition of two benzyl radicals to Sc 3 N@I h -C 80 .…”
Section: Angewandte Chemiesupporting
confidence: 63%
“…[1][2][3][4] Thec harge transfer from the internal unit to the fullerene cage gives rise to the important properties of EMFs.Based on the charge localized on the fullerene cage,two types of EMFs could be identified:o pen-shell EMFs with an unpaired electron residing on the cage or closed-shell EMFs containing only paired electrons.S ignificantly,o pen-shell EMFs have ahigh reactivity toward radical reactions because of their own radical character.F or instance,several insoluble mono-EMFs such as La@C 2n (2n = 72, 74, 80, 82) [5][6][7][8][9] were solubilized during a1 ,2,4-trichlorobenzene extraction process.T he discovery of these insoluble EMFs was achieved because these highly reactive,o pen-shell EMFs can be transformed into stable,c losed-shell derivatives through radical coupling reactions with dichlorophenyl radicals.A dditionally,t he reaction between La@C 82 and toluene [10] also revealed that the open-shell La@C 82 is able to convert into ac losed-shell derivative.S imilarly,a nu nexpected NO 2 radical addition occurred when anthranilic acid and isoamyl nitrite reacted with La@C 82. [1][2][3][4] Thec harge transfer from the internal unit to the fullerene cage gives rise to the important properties of EMFs.Based on the charge localized on the fullerene cage,two types of EMFs could be identified:o pen-shell EMFs with an unpaired electron residing on the cage or closed-shell EMFs containing only paired electrons.S ignificantly,o pen-shell EMFs have ahigh reactivity toward radical reactions because of their own radical character.F or instance,several insoluble mono-EMFs such as La@C 2n (2n = 72, 74, 80, 82) [5][6][7][8][9] were solubilized during a1 ,2,4-trichlorobenzene extraction process.T he discovery of these insoluble EMFs was achieved because these highly reactive,o pen-shell EMFs can be transformed into stable,c losed-shell derivatives through radical coupling reactions with dichlorophenyl radicals.A dditionally,t he reaction between La@C 82 and toluene [10] also revealed that the open-shell La@C 82 is able to convert into ac losed-shell derivative.S imilarly,a nu nexpected NO 2 radical addition occurred when anthranilic acid and isoamyl nitrite reacted with La@C 82.…”
mentioning
confidence: 99%
“…[3,4] These compounds have generated considerable recent research interest because of their potentiala pplicationsi nt he field of magneticr esonance imaging agents, molecular electronic devices, and solar cells. [5][6][7][8][9] Since the discovery of Sc 3 N@C 80 in 1999, [10] cluster fullerenes (CFs) have been of particular interest in the field of endohedral fullerenes as ar esult of their exceptionally high yield and excellent stabilitya nd the unique structural variety of both clusters and cages, which resultsi nt heir tunable physical and chemical properties. [11][12][13][14] To date,avariety of cluster fullerenes have been reported, including nitride (NCFs), [15][16][17] carbide( CCFs), [18,19] hydrocarbide (HCCFs), [20] oxide (OCFs), [21,22] sulfide( SCFs), [23][24][25] carbonnitride (CNCFs), [26,27] and di/trimetallic clusterf ullerenes.…”
Section: Introductionmentioning
confidence: 99%
“…Prime examples are the encapsulation of H 2 O inside C 60 , heavy atoms such as Ba in C 80 or more recently Pb in C 80 , endohedral fullerenes containing neon, argon, or heavier rare gas atoms, metal clusters such as La 2 in C 72 , or even another fullerene cage forming so‐called buckyonions with C 20+2 m @C 20+2 n ( m << n , m ≠ 1) . For a recent comprehensive review on endohedral fullerenes see Popov et al or Lu et al…”
Section: Introductionmentioning
confidence: 99%